2018
DOI: 10.1111/and.13161
|View full text |Cite
|
Sign up to set email alerts
|

Effects of varicocele on testicles: Value of strain elastography: A prospective controlled study

Abstract: The aim of this study was to evaluate the structural changes in testicles of the patients with varicocele by strain elastography (SE) and to identify the relationship between semen analysis and hormone levels considering SE results. The patients were separated into two groups as varicocele and control, according to their physical examination and the scrotal colour duplex ultrasonography results. All patients underwent examination by hormonal profile, semen analysis, colour duplex ultrasonography and sonoelasto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 27 publications
(31 reference statements)
0
9
0
Order By: Relevance
“…The discrepancy in the above findings is explicable considering that infertile men with severe damage to spermatogenesis and semen abnormalities may have similar histological changes in both testicles extending up to the degree of testicular failure. Similarly, two studies using strain elastography reported inverse elasticity readings in VC testicles in comparison to controls [ 18 , 19 ]. If infertility is absent, no difference might be found between VC-bearing and normal testicles as reported in one study [ 20 ].…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The discrepancy in the above findings is explicable considering that infertile men with severe damage to spermatogenesis and semen abnormalities may have similar histological changes in both testicles extending up to the degree of testicular failure. Similarly, two studies using strain elastography reported inverse elasticity readings in VC testicles in comparison to controls [ 18 , 19 ]. If infertility is absent, no difference might be found between VC-bearing and normal testicles as reported in one study [ 20 ].…”
Section: Discussionmentioning
confidence: 93%
“…Using real-time strain elastography, Salama et al [ 18 ] reported a significantly higher strain ratio and elasticity scores in infertile men with VC in comparison to normal controls, whereas in a second study, the left testicle strain ratio median value was found to be significantly lower in oligospermic men in comparison to a normal group [ 19 ]. In a study by Küçükdurmaz et al [ 8 ], dyspermic men including men with VC had different strain ratio readings in comparison to controls but the authors after sub-analysis concluded that the presence of VC did not have effect on elastography findings.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have reported that varicocele causes a decrease in testicular weight and volume (Guo et al., 2018; Lipshultz & Corriere, 1977), while in others it does not affect (Bitkin et al., 2019; Zhang et al., 2018). In the present study, although testicular weight decreased significantly in the V group compared with the other groups, there was no significant difference between the groups in terms of testicular volume.…”
Section: Discussionmentioning
confidence: 99%
“…The strain ratio of the testis, especially the left side, is elevated in case of varicocele, well before the atrophy of the testis. Consequently, SE could be useful to detect the damage caused by varicocele [7]. The testicular stiffness and semen parameters are known to be connected too.…”
Section: Introductionmentioning
confidence: 99%